Organotrialkoxysilane-mediated controlled synthesis of noble metal nanoparticles and their impact on selective fluorescence enhancement and quenching - Pandey, P.C.; Shukla, S.; Pandey, G.; Narayan, R.J. (AVS Science and Technology Society, 2020)
Ordered noble metal nanoparticles functionalized with organotrialkoxysilanes [e.g., 2-(3, 4-epoxycyclohexyl) ethyltrimethoxysilane (EETMS), 3-aminopropyltrimethoxysilane (APTMS), and 3-glycidoxypropyltrimethoxysilane (GPTMS)] were used as substrates to investigate the variation in fluorescence intensity of some well-known fluorophores (e.g., fluorescein, rhodamine, and l-tryptophan) based on distance effects and surface plasmonic activity. Anisotropic palladium nanoparticles (PdNPs), gold nanospheres (AuNPs), and silver nanospheres (AgNPs) were synthesized as a function of concentration of EETMS, APTMS, or GPTMS; the organotrialkoxysilane concentration directed the growth rate of particles along certain crystallographic facets. The reactive organic functionalities of alkoxysilanes facilitated the physisorption of probe molecules in proximity to the nanoparticles. The maximum enhancement in fluorescence intensity was observed in the case of APTMS-induced stabilization at hydrodynamic radii (RH) of ∼350 nm as a result of specific interactions with fluorescein molecules; quenching was mostly observed close for interactions between the GPTMS-functionalized nanoparticles and fluorophores. The smaller size of l-tryptophan and the absence of effective plasmonic coupling with PdNPs and AuNPs surfaces in the 290-370 nm emission range resulted in quenching; an appreciable far-field linking with AgNPs was noted around an emission wavelength of 360-375 nm, which resulted in several fold enhancement in intensity. Alkoxysilanes were shown to regulate the spatial control between the functionalized nanoparticles. As such nanoparticles, alkoxysilane-derived nanomaterials, may serve as promising platforms for metal enhanced fluorescence and fluorescence resonance energy transfer. © 2020 Author(s).